3z-19=123

Simple and best practice solution for 3z-19=123 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3z-19=123 equation:


Simplifying
3z + -19 = 123

Reorder the terms:
-19 + 3z = 123

Solving
-19 + 3z = 123

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + 3z = 123 + 19

Combine like terms: -19 + 19 = 0
0 + 3z = 123 + 19
3z = 123 + 19

Combine like terms: 123 + 19 = 142
3z = 142

Divide each side by '3'.
z = 47.33333333

Simplifying
z = 47.33333333

See similar equations:

| 2[t-(2t+8)+6]=2(t+2) | | 5x(x+8)+5x(6-x)=9(12+x)-8(7-x) | | 7(-6)(5)= | | 4z^2+3z-1=0 | | 2x^2-3y=32 | | -(z+7)+(5z+1)=5(z+1) | | 5x-19=3x+6 | | 3x(x+3)=24 | | 27x=33 | | 100-50= | | 8cosx-3=0 | | F(-1)=3x^3-5x^2-2x-5 | | 5x-2=125 | | 3x-7i=3(3x-7u) | | 8n+32=4(7n-7) | | (3a^3)(5a^2)= | | 2h=-3g+52 | | 2-3ln(x+1)=8 | | 3-2*-4=w | | 4(x+6)=6(x-2)+3x-4 | | y=2x^2-12x-19 | | (2x-1)+2(2x+6)=4x-1 | | (2p+3)(2p-3)=(2p+10)(2p-10)-91p | | 3h+13h=20-2 | | 6x+7=3x+8 | | 2x+3(x-2)=4x-24+2x | | 6*-2=r-5r | | 7(x-9)-5=-68 | | 6*-2=r | | 15x=482 | | 3y-1+y+35=7+7y+33-5y | | 8w+6w=82 |

Equations solver categories